Risk of HBV Reactivation in Patients With Resolved HBV Infection Receiving Anti-CD19 Chimeric Antigen Receptor T Cell Therapy Without Antiviral Prophylaxis - Li, Ping; Zhou, Lili; Ye, Shiguang; Zhang, Wenjun; Wang, Junbang; Tang, Xiaochen; Liu, Jie; Xu, Yangyang; Qian, Wenbin; Liang, Aibin (Frontiers in Immunology, 2021)
Background: Chimeric antigen receptor (CAR) T-cell therapy has emerged as a novel treatment modality for hematologic malignancies and is predicted to experience widespread use in the near future. However, not all risks associated with this novel approach are well defined. There are few data in the risk of HBV reactivation and limited experience in management in patients with resolved HBV infection who undergo CAR-T cell therapy. Methods: We performed a post-hoc analysis of a prospective clinical trial of anti-CD19 CAR-T (CART19) cell therapy in patients with relapsed or refractory (r/r) B-cell malignancies, and aimed at exploring the actual risk of HBV reactivation in a cohort of patients with resolved HBV infection receiving CART19 cell therapy in the absence of antiviral prophylaxis. Results: In this study, we investigated the risk of HBV reactivation after CART19 cell therapy in 30 consecutive patients with B-cell malignancies and resolved HBV infection without antiviral prophylaxis, in Tongji Hospital of Tongji University. In this cohort, 2 patients developed HBV reactivation 2 months and 14 months after CAR-T cell infusion, respectively, the latter of whom developed severe hepatitis. These findings showed that the incidence of HBV reactivation was 6.67% (95% CI, 0.8-22.1). Specifically, none of 21 patients who were HBsAb positive (0.0%) versus 2 of 9 patients who were HBsAb negative (22.2%) experienced HBV reactivation (p=0.03), suggesting HbsAb seronegativity at baseline is a possible risk factor in this population. Although use of tocilizumab or corticosteroids has been associated with increased risk of HBV reactivation, none of the patients who received these agents had HBV reactivation in this study. Conclusion: This is the first and largest study to assess the true incidence of HBV reactivation in patients with resolved HBV infection receiving CART19 cell therapy without antiviral prophylaxis. This study highlights that this population are at risk of developing HBV reactivation and indicates that close monitoring of HBV DNA is required in the absence of antiviral prophylaxis. In addition, antiviral prophylaxis is recommended in the HBsAb-negative subpopulation.